2019
DOI: 10.1111/jch.13759
|View full text |Cite
|
Sign up to set email alerts
|

Highly precise risk prediction model for new‐onset hypertension using artificial intelligence techniques

Abstract: It has been estimated that hypertension is the cause of approximately 13% of all deaths worldwide each year. 1 In light of the world's population growth and aging demographic, hypertension is a global burden, along with other cardiovascular and age-related diseases. 2,3 Early intervention with lifestyle modifications and treatment of "prehypertension" may reduce the incidence and long-term consequences of clinical hypertension. [4][5][6][7] Recent guidelines lowered the recommended thresholds for diagnosing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 30 publications
2
48
0
1
Order By: Relevance
“…The HOPE Asia Network has published a number of papers on important Asia‐specific topics in hypertension . This Asia‐specific issue of the Journal of Clinical Hypertension provides an important resource including original research and review articles on the management of hypertension from a variety of Asian viewpoints, including topics such as central BP, environmental factors, comorbidities such as diabetes, atrial fibrillation, heart failure, and dementia, recent Asian guidelines and so forth . This issue also includes reports from twelve countries/regions in Asia to help define and highlight the current status of hypertension, its management, and their initiatives.…”
Section: Resultsmentioning
confidence: 99%
“…The HOPE Asia Network has published a number of papers on important Asia‐specific topics in hypertension . This Asia‐specific issue of the Journal of Clinical Hypertension provides an important resource including original research and review articles on the management of hypertension from a variety of Asian viewpoints, including topics such as central BP, environmental factors, comorbidities such as diabetes, atrial fibrillation, heart failure, and dementia, recent Asian guidelines and so forth . This issue also includes reports from twelve countries/regions in Asia to help define and highlight the current status of hypertension, its management, and their initiatives.…”
Section: Resultsmentioning
confidence: 99%
“…Health data provide valuable information for AI applications in assisting health assessment and disease prognosis. Current evidence has revealed AI's efficacy on identification of hypertensive status, [12][13][14] prediction for incidence, [15][16][17] and outcomes from hypertension. 18,19 Masked hypertension, with a reported prevalence ranging from 9% to 30% 20,21 globally, persists as an obstacle for accurate hypertension diagnosis which mainly relies on elevated office blood pressure (BP) level.…”
Section: Pred I C Ti On For In Ciden Ce Hypertens I On or Its Rel Amentioning
confidence: 99%
“…Health data provide valuable information for AI applications in assisting health assessment and disease prognosis. Current evidence has revealed AI’s efficacy on identification of hypertensive status, 12‐14 prediction for incidence, 15‐17 and outcomes from hypertension 18,19 …”
Section: Prediction For Incidence Hypertension or Its Related Clinicamentioning
confidence: 99%
“… 31 Using data from 18 258 individuals, machine learning methods were able to develop a highly precise model to predict the development of hypertension in a general population. 34 This could be used to identify individuals at risk of developing hypertension and allow early intervention with tools such as lifestyle modification to prevent future hypertension development. Another artificial intelligence-based prediction model using multi-input multi-output deep neural networks based on time-series BP data and related contextual information showed that this approach has the potential to predict both mean BP and BPV.…”
Section: Potential For Digital Platforms and Artificial Intelligence mentioning
confidence: 99%
“… 32 In addition, the availability of big data collected by wearable BP monitoring could facilitate time-series analyses and be used to inform artificial intelligence strategies to predict hypertension. 33 , 34 …”
mentioning
confidence: 99%